Document management system portal (e-Tanah) / Amir Mujahid Sudarno - Sudarno, Amir Mujahid (Faculty of Computer and Mathematical Sciences, 2007)
Document management system is the automated control of electronic documents- page images, spreadsheets, word processing documents, and complex, compound documents - through their entire life cycle within an organization, from initial creation to final archiving, it allows organizations to exert greater control over the production, storage, and distribution of documents, yielding greater efficiencies in the ability to reuse information, to control a document through a workflow process, and to reduce product cycle times. The purpose of this study is intended to develop a Document Management System Portal for Gombak Land and Registry Office that is called E-Tanah. E-Tanah Portal uses Liferay Portal as the software because of its reliability and cost effective tools. Overall, this portal helps to improve customer satisfaction and benefit the organization in managing a better document management system solution for a better transaction in the Gombak Land and Registry Office.